RNA-Seq Revealed Novel Non-proliferative Retinopathy Specific Circulating MiRNAs in T2DM Patients - Li, Zimeng; Dong, Ying; He, Chang; Pan, Xingchen; Liu, Dianyuan; Yang, Jianli; Sun, Liankun; Chen, Peng; Wang, Qing (Frontiers in Genetics, 2019)
Background: Diabetic retinopathy (DR) is a common diabetes complication and was considered as the major cause of blindness among young adults. MiRNAs are a group of small non-coding RNAs regulating the expression of target genes, and have been reported to be associated with the development of diabetic retinopathy in a variety of molecular mechanisms. In this study, we aimed to identify miRNAs that are differentially expressed in the serum of DR patients. Methods: We recruited 21 type 2 diabetes mellitus (T2DM) inpatients of Chinese Han ancestry, consisted of 10 non-proliferative DR patients (DR group) and 11 non-DR T2DM patients (NDR group). MiRNA was extracted from fasting peripheral serum and quantified by RNA-seq. The expression levels of miRNA was evaluated and compared between the two groups, with the adjustment of age. The validated target genes of miRNAs were subjected to a pathway analysis. We also constructed a weighted polygenic risk score using the differentially expressed miRNA and evaluated its predictive power. Results: Five miRNAs were differentially expressed between DR and NDR groups (p value ≤ 0.01, LFC ≥ 2 or LFC ≤ -2). These included miR-4448, miR-338-3p, miR-190a-5p, miR-485-5p, miR-9-5p. In total, these miRNAs was validated to regulate 55 target genes. Four target genes were found to overlap with the NAD metabolism, sirtuin and aging pathway, which was thought to control the vascular growth and morphogenesis. The predictive power of our polygenic risk score was apparently high (AUC = 0.909). However, it needs to be interpreted with caution. Conclusion: In this study, we discovered novel DR-specific miRNAs in human serum samples. These circulating miRNAs may represent the pathological changes in the retina in response to diabetes and may serve as non-invasive biomarkers for early DR risk prediction.